CircERC1 facilitates chemoresistance through inhibiting pyroptosis and remodeling extracellular matrix in pancreatic cancer - Jian Zhang; Shengnan Lv; Xinyu Peng; Huan Liu; Jianxiong Guo; Ziyu Liu; Tongjia Chu; Han Liu; Kehang Duan; Fengxiang Lou; Yubo Chi; Bing Gao; et al. (Molecular Cancer)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) resists to neoadjuvant treatment even though overall survival (OS) is transiently prolonged while the underlying mechanism of this drug resistance remains elusive. Methods Gemcitabine combined with Nab-paclitaxel (GEM-NabP) treated PDAC tissues-derived EVs were isolated and underwent circRNA sequencing. CircERC1 was identified as an EVs-packaged circRNA that regulates PDAC progression and tumor microenvironment (TME) in vitro and in vivo with the help of EdU, colony formation, SRB viability assays, transwell assays and PET-CT analysis. The underlying mechanism was substantiated by qRT-PCR, Western blot, RNA pull-down, mass spectrometry, RNA immunoprecipitation and Co-immunoprecipitation. In addition, single-cell RNA sequencing was adopted to analyze the TME and immunohistochemistry, dual luciferase reporter assay were performed to validate the results. Results CircERC1 biogenesis is activated by QKI after GEM-NabP treatment. It interacts with hnRNPA1 and promotes its ubiquitination degradation by blocking its SUMOylation at K183. The degraded hnRNPA1 fails to upregulate PKM2, a crucial activator of NLRP3 inflammasome, thereby inhibiting Caspase1-GSDMD mediated pyroptosis. Furthermore, EVs-packaged circERC1 enhances extracellular matrix (ECM) deposition and hindering drug and immune cells infiltration in cancer associated fibroblasts (CAFs) in PDAC microenvironment. Conclusions Our findings reveal a novel circERC1 as a key regulator in PDAC-secreted EVs following paclitaxel (PTX) treatment, thereby inhibiting gemcitabine/Nab-paclitaxel (GEM-NabP) induced pyroptosis. Our results highlight a potential therapeutic target for overcoming chemoresistance and remodeling pancreatic TME.